2022
DOI: 10.1145/3526117
|View full text |Cite
|
Sign up to set email alerts
|

A Cyber-physical Approach for Emergency Braking in Close-Distance Driving Arrangements

Abstract: In addition to fuel/energy savings, close-distance driving or platooning allows compacting vehicle flows and, hence, increasing throughput on congested roads. The shorter the inter-vehicle separation is in such settings, the more the benefits. However, it becomes considerably harder to guarantee safety, in particular, when braking in an emergency. In this paper, we are concerned with this problem and propose a cyber-physical approach that considerably reduces the stopping distance of a platoon with inter-vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In our previous work [19], we showed that this communication latency must be accounted for to avoid collisions within the platoon during emergency braking in a dense vehicle scenario that induces both high levels of data and road traffic. Murthy and Masrur propose leveraging the space buffer between vehicles in a heterogeneous platoon during emergency braking on a flat road [10] or in a downhill [18]. To this end, the authors propose that if a platooning vehicle cannot brake at its assigned deceleration rate on a downhill road, it sends distress messages so that the other vehicles can adapt their deceleration rates to the one under distress.…”
Section: Background and Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work [19], we showed that this communication latency must be accounted for to avoid collisions within the platoon during emergency braking in a dense vehicle scenario that induces both high levels of data and road traffic. Murthy and Masrur propose leveraging the space buffer between vehicles in a heterogeneous platoon during emergency braking on a flat road [10] or in a downhill [18]. To this end, the authors propose that if a platooning vehicle cannot brake at its assigned deceleration rate on a downhill road, it sends distress messages so that the other vehicles can adapt their deceleration rates to the one under distress.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In contrast, instead of dissolving the platoon, we propose to switch between controllers and/or adjust inter-vehicle gaps proportionally with the levels of communication outages in this paper. The works in [10], [19], and [18] emphasize minimizing the stopping distance of the LV in addition to avoiding collisions between the FVs to attain a fail-safe state. However, to the best of our knowledge, the transition from fail-operational states to emergency braking states leading to a fail-safe state is not considered in previous works.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations